Clinico-pathological Presentation of Gastroenteropancreatic Neuroendocrine Tumours and Immunohistochemical Study with Synaptophysin and Chromogranin - Jagan Balu; Subramanian Sankar; P Suresh; K Sreenivasan; Babu Elangovan (Journal of Clinical and Diagnostic Research, 2019)
Introduction: Neuroendocrine Tumours (NETs) have lethargic clinical courses, the majority of the NETs take place in the gastrointestinal tract and most of Gastrointestinal Neuroendocrine Tumours (GNTs) cases are asymptomatic. The diagnosis is based on clinical features, biochemical analysis, imaging, and confirmation with histopathology. Aim: To analyse the clinico-pathological aspects, and immunohistochemical study with synaptophysin, chromogranin and Ki-67 index to grade the GNTs. Materials and Methods: In this prospective study, during March 2017 to June 2018 a detailed history for every enrolled patients was taken and thorough clinical examination was done for those diagnosed with gastroenteropancreatic neuroendocrine tumour, a database was created which accounts for data collection which included sex, age, and clinical appearance, past medical history, investigations, drug history, treatment and outcome. For immunohistochemical staining, three antibodies chromogranin A, synaptophysin, and staining of Ki-67, a widely-used proliferation marker was performed. Ki-67 index was calculated as the percentage of 2,000 tumour cells from the areas of highest nuclear labeling. Results: This study had 47 patients with clinical presentations and classical radiological appearance of NET of which 43 patients were diagnosed with NET using biopsy. Majority of patients were in age group of 41 to 60 (40.5%) and above 60 years of age (42.5%). Duodenum being the common site with 40% followed by stomach with 17% and pancreas with 15%. Most common grade of NET was Grade 1 (95%) followed by a Grade 2 (5%). Among 47 patients, 19 patients underwent duodenal polypectomy for duodenal polyp in the first part of duodenum. The positivity rate for synaptophysin, and chromogranin was 97% and 90.5%. Ki-67 index was <2% in 95% of the cases, it was <5% in 5% of the cases. Conclusion: In this study we analysed the clinicopathological details of 47 patients including immunohistochemical characteristics of 43 NET. NETs of the GIT known to be rare tumours, presents with increased incidence over the recent decades, most probably due to the increased awareness among the physicians and improved diagnostic techniques.